THE SPEECH ACTS IN LA NACION’S LETTERS TO THE EDITOR - Cuvardic García, Dorde (2013)
Letters to the editor is a modality of participative journalism that allows the establishment of communicative bonds among readers, media and other actors of the public space of discussion. In this article an analysis of Letters to the column of La Nación is made from the pragmatic theory of the speech acts. Interest is centered in establishing the intentions of the readers who send these messages to the newspaper.